Powerless - Cody, Matthew (Yearling, 2011)
Daniel and his family move to a new town where he meets six kids who have superpowers. The townsfolk are unaware that it is these young people who have been protecting their town. Now their powers are fading as they reach thirteen and Daniel is drawn into a search for the supervillain who is stealing their powers.